ANALISIS FRAUD DIAMOND DALAM MENDETEKSI FINANCIAL STATEMENT FRAUD : STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2010-2012 - Kennedy Samuel Sihombing; Shiddiq Nur Rahardjo (Diponegoro Journal of Accounting, 2014)
Financial statements become an important instrument in the operations of a company. Company's financial condition may be reflected in the financial statements. However , there are many loopholes in the financial statements which can become a chance for the management and certain parties to commit fraud  on the financial statements. This study was conducted to analyze the effect of the Development variables of fraud triangle by Cressey, the fraud diamond proposed by Wolfe and Hermanson (2009) that financial targets, financial stability, external pressure, nature of industry, ineffective monitoring, change in auditors, rationalization and capability towards the financial statement fraud which proxied by earnings management .The samples used in this study are 51 manufactured company that listed in Indonesia Stock Exchange during the period 2010-2012. The type of data used are secondary data, in the form of annual reports of companies listed on the Stock Exchange during the period 2010-2012 . Hypothesis testing was conducted using multiple linear regression with SPSS 21 software .The results showed that the variables of financial stability which proxied by change in total assets ratio, external pressure variables which proxied by leverage ratio, nature of the industry which is proxied by the change in receivables ratio and rationalization variables which proxied by the change in total accruals ratio shown to affect the financial statement fraud. This study does not prove that financial targets variables which proxied by ROA(Return On Asset), ineffective monitoring variable which proxied by the ratio of independent board , change in auditors , and capability which is proxied by the change of directors has an influence on the financial statement fraud .